2017
DOI: 10.1097/mej.0000000000000392
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of patients with syncope seen in the emergency room department: an evaluation of four different risk scores recommended by the European Society of Cardiology guidelines

Abstract: Although a large number of events occur after syncope, the risk scores recommended by guidelines overestimate risk, but there were no statistically significant differences between observed and predicted risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Of the 692 articles found in the updated literature search, three additional articles by Sandhu et al, Baron-Esquivias et al, and Du Fay De Lavallaz et al were found and included in our systematic review. [19][20][21] The articles by Du Fay De Lavallaz et al and Baron-Esquivias et al reported outcomes beyond one year and did not explicitly report one-year outcomes. The authors did not respond to our attempts to clarify the data.…”
Section: Literature Searchmentioning
confidence: 99%
“…Of the 692 articles found in the updated literature search, three additional articles by Sandhu et al, Baron-Esquivias et al, and Du Fay De Lavallaz et al were found and included in our systematic review. [19][20][21] The articles by Du Fay De Lavallaz et al and Baron-Esquivias et al reported outcomes beyond one year and did not explicitly report one-year outcomes. The authors did not respond to our attempts to clarify the data.…”
Section: Literature Searchmentioning
confidence: 99%